“Lo que pasó en Ciespal” Apuntes etnográficos sobre el poder, los medios y los sin-sentidos de la violencia - Hurtado Arroba, Edison (2005)
Based on ethnography, the article presents a political approach to the events occurred in Ciespal on April 20, 2005, the day of Lucio Gutierrez overthrow. Opposed to representations and stigmatizations that have been woven into the political fight, the text constructs three parallel perspectives: a) an institutional one, in which power is re-established, b) one of the non-sense, in which violence is stigmatized, and c) a phenomenological one, in which actors guide themselves by a logic of practice. The central argument is built from the relation between violence and politics: it explains that violent attitudes against politicians, far from being irrational or chaotic, as some media has put it, were loaded of a practical-moral rationality expressed in the indignation of population against politicians. Following Benjamin, it concludes in an attempt to understand the senses of the political violence: that violence of the order that tries to conserve itself, and that violence of the demonstrators that displays slightly signs of a substantive political change.